Wheat biocomposite extraction, structure, properties and characterization: A review - Mohammed A.A.B.A.; Borhana Omran A.A.; Hasan Z.; Ilyas R.A.; Sapuan S.M. (MDPI, 2023)
Biopolymers; Composite materials; Packaging materials; Starch; Toxic materials; Biocomposite; Biocomposite materials; Material packaging; Natural ingredients; Structure characterization; Structure property; Wheat biocomposite; Wheat fiber; Wheat gluten; Wheat starch; Fibers